Affective exchanges and maternal goals of socialization of emotions. - Bieler, Clarice; Leal Fernandes Mendes, Deise Maria (Revista de Psicologia, 2023)
Affective exchanges favor early development and can be impacted by maternal goals. This study has investigated affective exchanges and attempts at affective exchanges, maternal emotional socialization goals, and associations among these domains. Observations of 20 mothers and babies (two/three months old) in Rio de Janeiro have been filmed and the mothers have been interviewed. Video and content analyses have been performed and the results indicated, on average, 5.5 changes and 13.8 attempts per dyad, and 2.38 shifts per change. The mother has been the one who has most frequently promoted affective exchanges (90%) and attempts at affective exchanges (99%), by means of speech. In the exchanges, the baby’s smile has been the predominant emotional expression, and among the maternal affective behaviors, speech. The analysis of the interviews has indicated valuing autonomy goals, valuing close relationships, without being found associations between maternal goals and characteristics of the analyzed exchanges. A certain complexity is already present in the mother-baby affective exchanges at the time of the development and the context studied. New studies should explore diverse sociodemographic contexts and variables.